A Survey on Achievement Motivation among University Students - Abdul Rashid Abdul Aziz; Amin Al-Haadi Shafie; Ishaq Ibrahim; Siti Nubailah Mohd Yusof; Nur Kareelawati Abd Karim; Husin Sungkar (Human Resource Management Academic Research Society, 2024)
Vol 12, Issue 3